Antimicrobial resistance and epidemiological patterns of Streptococcus pyogenes in Türkiye - Nihan Ünübol; Nese Caglayan; Sinan Cebeci; Yeşim Beşli; Banu Sancak; Neval Yurttutan Uyar; Siavosh Salmanzadeh Ahrabi; Masoud Alebouyeh; Tanıl Kocagöz (Journal of Infection and Public Health)
Background: Drug-resistant Group A beta-hemolytic streptococci remain significant infectious agents globally. This study investigated the major S. pyogenes strains responsible for infections in Türkiye and their susceptibility to beta-lactam and macrolide antibiotics. Methods: We determined the minimum inhibitory concentration using the penicillin gradient test and performed emm typing and DNA fingerprinting via pulsed-field gel electrophoresis (PFGE) to analyze the clonal spread of 92 S. pyogenes strains isolated from two hospitals in Türkiye between 2020 and 2022. Results: Our findings revealed the predominant S. pyogenes strains causing infections in the population and provided insights into the epidemiological relatedness of these drug-resistant strains. This study also evaluated the correlation between emm typing and PFGE in tracking S. pyogenes epidemiology. In this study, the current resistance patterns of S. pyogenes strains in Türkiye identified erythromycin resistance in a few strains, but no resistance to penicillin was detected. Conclusions: This study revealed that emm types 1, 12 and 89 as S. pyogenes strain genotypes were responsible for epidemic infections in Türkiye. PFGE genotyping and emm typing were found to provide better phylogenetic classification in the investigation of S. pyogenes epidemiology.